2017
DOI: 10.1002/lary.26666
|View full text |Cite
|
Sign up to set email alerts
|

Novel murine xenograft model for the evaluation of stem cell therapy for profound dysphagia

Abstract: MDSCs exhibited over 100% survival at 3 months when injected into an immune-deficient hemiglossectomy mouse model. Tongue-injured animals injected with MDSCs exhibited superior weight gain after hemiglossectomy than control animals (P < .05). These data support further investigation into the use of autologous MDSCs as a potential treatment for dysphagia secondary to tongue weakness and fibrosis LEVEL OF EVIDENCE: NA Laryngoscope, 127:E359-E363, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…19 Kuhn et al later demonstrated survival of human muscle-derived cells injected into the tongue ofimmune-deficient mice post-hemiglossectomy. 13 Animals injected with MDCs weighed significantly more than control animals 12 weeks after treatment, suggesting improved alimentation. Plowman et al examined the effects of autologous muscle-derived stem cells in a denervated ovine tongue model.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…19 Kuhn et al later demonstrated survival of human muscle-derived cells injected into the tongue ofimmune-deficient mice post-hemiglossectomy. 13 Animals injected with MDCs weighed significantly more than control animals 12 weeks after treatment, suggesting improved alimentation. Plowman et al examined the effects of autologous muscle-derived stem cells in a denervated ovine tongue model.…”
Section: Discussionmentioning
confidence: 94%
“…[7][8][9][10]18 Several studies have reported the formation of new muscle fibers following the injection of muscle-derived progenitor cells in a rodent hemiglossectomy model. [11][12][13] Kim et al injected a hydrogel-myoblast composite in a rat hemiglossectomy model and observed significant increase in tongue weight, evidence of neovascularization, and possible neurotization. 12 Their results were supported by a study conducted by Bunaprasert et al, who reported that rats receiving myoblast transplantation, whether via gel suspension or in the form of undifferentiated or differentiated constructs, showed superior quality of the muscular regenerate compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 More recently, cell therapy with autologous myoblasts for radiation induced tongue atrophy has been investigated. 6 , 9 In 2022, Schar et al, described a novel surgical treatment which uses hyaluronic acid and lipofilling for pharyngeal tongue base augmentation. 10 They report increased pharyngeal pressure and improved dysphagia symptoms postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, human cells have been investigated in immune-deficient rodents, taking a step closer to human translation. Kuhn et al[ 23 ] demonstrated persistence of human MDSCs injections in immune deficient mice. MDSC survival was assessed using in vivo imaging to visualize luciferase-transduced MDSCs.…”
Section: Stem Cell Therapies For Tongue Dysfunctionmentioning
confidence: 99%